Physiological analysis of the improved [epsilon]-polylysine production induced by reactive oxygen species - Yue, Chaoping; Su, Zhiwei; Tai, Baoyan; Tang, Hui; Da, Wangbao; Xu, Hongli; Zeng, Huawei; Xin, Bingyue; Zeng, Xin (Applied microbiology and biotechnology, 2023)
Epsilon-poly-L-lysine ([epsilon]-PL) is produced by Streptomyces species in acidic and aerobic conditions, which inevitably induces rapid generation of reactive oxygen species (ROS). The devastating effects of ROS on biomolecules and cell vitality have been well-studied, while the positive effects of ROS are rarely reported. In this study, we found that a proper dose of intracellular ROS (about 3.3 [mu]mol H.sub.2O.sub.2 /g DCW) could induce a physiological modification to promote the [epsilon]-PL production (from 1.2 to 1.5 g/L). It resulted in larger sizes of colony and mycelial pellets as well as vibrant, aggregated, and more robust mycelia, which were of high capability of ROS detoxication. Physiological studies showed that appropriate doses of ROS activated the metabolism of the pentose phosphate pathway at both transcriptional and enzymatic levels, which was beneficial for biomass accumulation. The biosynthesis of lysine was also promoted in terms of transcriptional regulatory overexpression, increased transcription and enzymatic activity of key genes, larger pools of metabolites in the TCA cycle, replenishment pathway, and diaminoheptanedioic acid pathway. In addition, energy provision was ensured by activated metabolism of the TCA cycle, a larger pool of NADH, and higher activity of the electron transport system. Increased transcription of HrdD and pls further accelerated the [epsilon]-PL biosynthesis. These results indicated that ROS at proper intracellular dose could act as an inducing signal to activate the [epsilon]-PL biosynthesis, which laid a foundation for further process regulation to maintain optimal ROS dose in industrial [epsilon]-PL production and was of theoretical and practical significance.